2010
DOI: 10.1177/0022034510375825
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial on Root Caries Prevention in Elders

Abstract: Root caries is common in institutionalized elders, and effective prevention methods are needed. This clinical trial compared the effectiveness of four methods in preventing new root caries. From 21 residential homes, 306 generally healthy elders having at least 5 teeth with exposed sound root surfaces were randomly allocated into one of four groups: (1) individualized oral hygiene instruction (OHI); (2) OHI and applications of 1% chlorhexidine varnish every 3 months; (3) OHI and applications of 5% sodium fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
207
1
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(235 citation statements)
references
References 22 publications
5
207
1
13
Order By: Relevance
“…SDF comprises of high concentrations of fluoride and Ag, thus one can anticipate greater efficacy in preventing root dentin caries 3) . However, SDF results in a strong browning of dentin surface and gingiva, thereby causing esthetic concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SDF comprises of high concentrations of fluoride and Ag, thus one can anticipate greater efficacy in preventing root dentin caries 3) . However, SDF results in a strong browning of dentin surface and gingiva, thereby causing esthetic concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Among treatments of NaF, acidulated phosphate fluoride (APF), and silver diamine fluoride (SDF), SDF was the most effective 3,4) . It is unique in terms of anti-bacterial [5][6][7] and anti-enzymatic effects 8) with silver ions (Ag + ) in addition to the demineralization inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the access to approximal RCLs for restorative management is limited or requires extensive removal of sound dental hard tissues. Therefore, several approaches to prevent initiation (Burt et al 1986;Mojon et al 1998;Tan et al 2010) or inactivate RCLs (Papas et al 2007;Ekstrand et al 2013) have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that silver diamine fluoride (SDF) is more effective in preventing root caries than are NaF varnish and chlorhexidine 27) . Sugawara et al 28) carried out an in vitro study using the Cariotester to evaluate the effect of SDF in inhibiting dentin demineralization.…”
Section: Discussionmentioning
confidence: 99%